Influence of Order of Reinstatement, Order of Compensationon Human Resource Management Practices in Selected State Corporations in Kenya - Kinyua, Zacchaeus Muriithi; Minja, Prof. David M.; Kiruthu, Dr. Felix (European Journal of Business and Strategic Management, 2016)
Purpose: The main purpose of this study was to examine the effect of order of reinstatement and order of compensation on the HRM practices in state corporations in Kenya. Methodology: This study employed an explanatory research design. The study population comprised of 200 court decisions in the Industrial Court relating to cases falling under the purview of Human Resource Management and these cases covered the period from 2013 to 2015. The rationale for this period is because the Constitution was promulgated in 2010. The new Constitution has provisions relating to fundamental rights and labour laws that govern and affect Human Resource Management. The cases filed in the Industrial Court after the new Constitution came into force were not determined immediately, hence the need for the study to deal with decisions made from 2013 to 2015. This study used simple random sampling design to sample the state corporations whereby the human resource manager was selected to represent a state corporation. The sample size was 84 respondents. The study used a questionnaire to obtain primary data. The research collected data by use of questionnaires. The questionnaire was self administered. A pilot study was conducted in order to establish the validity and reliability of data collection instruments. Data collected from the questionnaires was prepared and converted from responses to quantitative format for ease in analysis using statistical package for social sciences (SPSS).The statistics generated was descriptive statistics and inferential statistics. The specific descriptive statistics included percentages and frequencies while the specific inferential statistics included a regression. A multiple linear regression model was used to test the significance of the influence of the independent variables on the dependent variable. The results were presented in form of tables and charts. Results: The study findings showed that order of reinstatement and order of compensation affects the human resource practices in State Corporation in Kenya. Unique contribution to practice and policy: Based on the findings of the study, the study recommended that Human resource managers in state corporations ought to take the initiative to access the information about laws that govern human resource practices in Kenya.